National Institute of Oceanography, Regional Center, Cochin-682 018, Kerala. - SANTHAKUMARI, V. (Journal of Indian Fisheries Association, 2015)
Distribution of zooplankton along two transects at Karwar and Ratnagiri off Kama taka, west coast oflndia, was studied. The standing stock of zooplankton was relatively high in the neritic zone with the highest value (358m/ 100m3) in the area off Ratnagiri due to the aggregationÂ ofÂ fish larvae and hydromedusae. Maximum zooplankton production in these areas was noticed with the low temperature and low dissolved oxygen during postmonsoon season. At Karwar the highest biomass (188 ml/100m3) was observed from the nearshore station due to swarms of the cladoceran Penilia avirostris and the pteropodCresis acicula when the salinity was low. The fluctuations in numerical abundance and percentage composition of all the major planktonic groups are di cussed. The fisheryÂ of these areas is compared with the zooplankton standing stock.